Kleptocracy and tax evasion under resource abundance. (2nd April 2019) - Mohtadi, Hamid; Ross, Michael L.; Jarrett, Uchechukwu; Ruediger, Stefan
Abstract: Evidence has shown that petroleum wealth is associated with less transparency and at the same time less tax collection. In this paper, we find that the two issues are linked through the citizens' tax evasion behavior. We develop a model to explain this link and conduct extensive empirical tests of its validity. The explanation is that officials tradeoff greater transparency to improve tax compliance against less transparency to increase gains from corruption. Oil windfalls diminish tax revenue needs, causing officials to optimize on less transparency. Seeing this, citizens optimize on a lower level of tax compliance. At equilibrium, both decline with a positive oil shock. We also study the alternative channel in which tax compliance responds to enforcement. Transparency is found to be the more robust channel. Ignoring citizens' strategic behavior would lead to predicting suboptimal investment in state capacity for tax enforcement. Using giant oil discoveries data combined with oil price data, we develop a dynamic composite instrument and estimate the model with a dynamic panel system generalized method of moments. We find robust support for our explanation and the model's deep structure for 130+ countries and the 1980–2010 period.